3-Nitrochromenes in the synthesis of fused- and spiro scaffolds: Recent progress. Issue 5 (4th March 2022) - Das, Suven
Abstract: The chromene core is one of the most privileged heterocyclic rings, which not only exists in natural products, but also found in synthetic compounds with remarkable biological activities. Especially, 3-nitrochromenes represent an important class of organic compounds because of their easy availability and versatile reactivity for the construction of complex molecular architectures. The present review emphasizes recent advances (2017–2021) in the synthesis of various fused- and spiro scaffolds involving 3-nitrochromene derivatives. In this context, regio- and stereoselective formation of important heterocyclic skeletons are discussed highlighting their reaction mechanism. Interestingly, spiro-chromeno heterocycles have been accomplished based on multicomponent reaction (MCR) strategy. Some of the synthesized compounds exhibit promising biological profile including anticancer activity. Graphical Abstract: UF0001